2018
DOI: 10.1093/gigascience/giy073
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis phenotyping through geometric morphometrics

Abstract: BackgroundRecently, great technical progress has been achieved in the field of plant phenotyping. High-throughput platforms and the development of improved algorithms for rosette image segmentation make it possible to extract shape and size parameters for genetic, physiological, and environmental studies on a large scale. The development of low-cost phenotyping platforms and freeware resources make it possible to widely expand phenotypic analysis tools for Arabidopsis. However, objective descriptors of shape p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 72 publications
(111 reference statements)
1
25
0
Order By: Relevance
“…The visualization of the body shape differences, associated with other groups of correlated morphological traits, allowed to obtain a clear diagnosis of sh morphology for each population [43,44]. Visualization tools might help in further study of the putative underlying mechanisms involved [45]. The result of the present study is in line with other studies based on truss analysis [4,[46][47][48][49] and geometric morphometrics [50,51] which have shown the sh species to have a distinctive morphology.…”
Section: Discussionsupporting
confidence: 83%
“…The visualization of the body shape differences, associated with other groups of correlated morphological traits, allowed to obtain a clear diagnosis of sh morphology for each population [43,44]. Visualization tools might help in further study of the putative underlying mechanisms involved [45]. The result of the present study is in line with other studies based on truss analysis [4,[46][47][48][49] and geometric morphometrics [50,51] which have shown the sh species to have a distinctive morphology.…”
Section: Discussionsupporting
confidence: 83%
“…Nevertheless, the tangent distances of specimens to the most outlying taxon, the common dolphin, were consistently slightly less than the partial Procrustes distances for the same pairwise comparisons, suggesting that there was some subtle effect of the distortion due to tangent projection for the extreme comparisons. In recent years, a number of studies have computed similar correlations between pairwise Procrustes and tangent distances among landmark configurations in diverse organisms and consistently found that these correlations were extremely close to 1.0 (Pretorius and Scholtz 2001;Polly 2002;Frost et al 2003;Fontaneto et al 2004;Lockwood et al 2004;McNulty 2004;Viscosi and Cardini 2011;Bai et al 2012;De Meulemeester et al 2012;Renner 2012;Neustupa 2013;Siver et al 2013;Ullmann et al 2017;Manacorda and Asurmedi 2018). Rohlf (1999) commented that he was not aware of any reports of biological datasets where the tangent projection did not provide a satisfactory approximation (with the exception of inadvertent inclusion of reflected specimens in the data).…”
Section: Tangent Space Approximation To Shape Spacesmentioning
confidence: 99%
“…These discoveries were only possible through the development of a technological infrastructure that allowed us to acquire genomic information at a large scale (Schuster, 2007). While many researchers have argued that phenomics -large scale phenotyping -will bring about a similar revolution in biology, most approaches for collecting high-throughput phenotypic data developed so far are system-specific and difficult to generalize (see Kristensen et al, 2008;Falkingham, 2012;Boyer et al, 2011;Hsiang et al, 2018;Manacorda and Asurmendi, 2018), with the notable exception of sub-cellular phenotypes (e.g., Clish, 2015). As a consequence, for most study systems, phenotyping methods remain low-throughput and can only be applied on a small scale (Houle, Govindaraju, and Omholt, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A promising way to collect high-throughput phenotypic data is to automate landmark data collection using computer vision techniques (e.g., Manacorda and Asurmendi, 2018). Automated landmarking has become the gold standard in human facial landmarking for both biomedicine (Porto et al, 2019) and, more notoriously, social networking websites and software developed for mobile phones (Kazemi and Sullivan, 2014), but its application in geometric morphometrics has remained restricted (Manacorda and Asurmendi, 2018;Vandaele et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation